Measurement of riverbank erosion rates of Pusu River using erosion pins method - Mohd Rosli, Nur Aqilah; Ibrahim, Saerahany Legori; Handan, Rabitah; Salleh, Md Noor (Penerbit UTHM, 2021)
Riverbank erosion is a major concern in all parts of the world due to its extensive impacts geomorphologically and economically. This study aims to quantify the rates of riverbank erosion of Pusu River using erosion pins method. Two sections of the river were selected namely site A and site B where site A is a straight section while site B is situated on the outside bend. 21 pins were installed at each site in a grid pattern. Measurement of erosion pins exposure were taken from February 2019 to April 2019. Field observation were made to identify the possible factors influencing the bank erosion. The average rates of bank erosion ranged between 0.05 cm/day to 0.21 cm/day at site A and 0.09 cm/day to 0.51 cm/day at site B. Bank failure occurred at site B towards the end of measurement period due to high flow after heavy rainfall event. Field observations suggest that rates of riverbank erosion were influenced by several factors such as the flow velocity and vegetative cover of the bank.